The awareness of Islamic inheritance / Siti Nurain Mohamed Ridzuan - Mohamed Ridzuan, Siti Nurain (2013)
Whenever a person dies, the asset of the deceased will be distributed to the person entitles to it. This situation has embarked the development of wealth management with the aims to manage the distribution. Islamic Law of Inheritance becomes the major guidance on wealth distribution for Muslims since it is parallel with the objective of Islam that is to ensure equality. It has been implemented in various countries including Malaysia. Referring to this, a study of Islamic Law of Inheritance is conducted with the objective to measure the level of awareness among Muslim community regarding the Islamic inheritance. Primary data is collected by distributing the questionnaires to the sample consist of 100 respondents that selected randomly within the area of Kuala Lumpur in order to collect the information needed in the study. It is expected that the level of awareness among Muslim community regarding Islamic inheritance is between the ranges of low to medium level